2018
DOI: 10.1161/strokeaha.117.019701
|View full text |Cite|
|
Sign up to set email alerts
|

Presence of Anterior Communicating Artery Aneurysm Is Associated With Age, Bifurcation Angle, and Vessel Diameter

Abstract: The presence of Acom aneurysm is significantly associated with patient age, wider angles of the anterior cerebral artery bifurcation, and smaller vascular diameter of the anterior communicating complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 24 publications
6
48
0
Order By: Relevance
“…3D rotational angiography, MRA, CTA) dealing with the problem of bifurcation angle morphology showed that wide bifurcation angle constitutes a significant risk factor for aneurysm formation. Those studies included the bifurcations which are generally considered to be predisposed for aneurysm development: ACoA complex 8,16,[34][35][36] , BA 14,29,37 and MCA 30,38 . Our findings are consistent with the results of the studies mentioned above; our present study showed that Φ 1 , Φ 2 and α angles in aneurysmal MCA bifurcations were significantly wider than in contralateral and control bifurcations.…”
Section: Discussionmentioning
confidence: 99%
“…3D rotational angiography, MRA, CTA) dealing with the problem of bifurcation angle morphology showed that wide bifurcation angle constitutes a significant risk factor for aneurysm formation. Those studies included the bifurcations which are generally considered to be predisposed for aneurysm development: ACoA complex 8,16,[34][35][36] , BA 14,29,37 and MCA 30,38 . Our findings are consistent with the results of the studies mentioned above; our present study showed that Φ 1 , Φ 2 and α angles in aneurysmal MCA bifurcations were significantly wider than in contralateral and control bifurcations.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior vasculature is more capable of arterial remodeling compared to the anterior vasculature [ 11 ]. The branching site is more vulnerable to hemodynamic stress because of the deflection and oscillation of blood flow [ 12 ], and cerebral aneurysms occur preferentially at arterial bifurcations.…”
Section: Structure Of the Cerebral Arterymentioning
confidence: 99%
“…Cerebral aneurysms preferentially occur at the anterior communicating artery, the posterior communicating artery, the middle cerebral artery bifurcation, and the basilar artery bifurcation where local shear stress is greatest on the arterial wall [ 12 , 29 ]. Blood flow at the arterial junctions, the bifurcations with wider bifurcation angles, or abrupt vascular angles are the most turbulent, and the shear stresses in these areas are the greatest.…”
Section: Pathophysiology Of a Cerebral Aneurysmmentioning
confidence: 99%
“…In fact, there are several publications that identify vessel diameters of daughter vessels as well as asymmetry in bifurcations as a risk factor for aneurysm rupture. [28,30] In contrast, other studies could not confirm this correlation between the distal vascular diameter or asymmetries and the risk of rupture. [6,13] In general, aneurysms of the posterior region are associated with an increased risk of rupture [10,15,25] and are also significantly associated with worse clinical outcomes, independent of the treatment modality.…”
Section: Introductionmentioning
confidence: 82%
“…[16] The surrounding vasculature was of particular interest in this case because their anatomical changes can demonstrably influence the local flow dynamics. [3,23] Recent studies revealed a wider bifurcation angle, including the medial cerebral artery (MCA) [1], the anterior cerebral artery (ACA) [28], and the basilar artery (BA) [29], can alternate the flow dynamics and promote the formation of local aneurysms. In basilar tip aneurysms (BTAs), an increased posterior cerebral artery (PCA) angle has been reported to be associated with the risk of aneurysm rupture.…”
Section: Introductionmentioning
confidence: 99%